RETHINKING GENDER DISCRIMINATION: THE RESTRICTION OF PAKISTAN WOMEN’S RIGHTS THROUGH CULTURAL AND POLITICAL INTERESTS AS PORTRAYED IN AISHA SAEED’S AMAL UNBOUND - Elah Patimah; Tri Septa Nurhantoro; Dwi Lisa Susanti (JELLT (Journal of English Language and Language Teaching), 2021)
Gender bias is a problematic issue until today. World has been accepted and convinced that gender is socially constructed, but society grows with a confusion of gender bias that leads to an endless feminist movement. A case on gender discrimination occurs in Pakistan, where inequality needs attention as it has been intersected with cultural and political practices. This seems to restrict any effort regarded to equality. This research aims to identify manifestations of gender discrimination experienced by the main character in Amal Unbound and to analyze aspects of cultural and political matters related to the restriction of Pakistan women. This research applied a descriptive qualitative method in the analysis. The data were analyzed by using Butler's concepts on gender. The findings indicate that the main character experienced various manifestations of gender discrimination, such as marginalization, subordination, stereotype, and violence. She has been in a worse condition as being restricted by practices of constructed culture and politics in Pakistan.